STRUCTURE IDENTIFICATION OF LEMBANG FAULT (DAGO GIRI TRACK) BASED ON 1 DIMENSIONAL MODELING MAGNETOTELURIC METHOD - Yosafat, Dippos
Earthquake is a geological event that occurs due to tectonic or volcanic activity. Earthquakes due to tectonic activity are caused by movements that occur in earth's crust. One of the causes of tectonic activity is faults. Lembang Fault is located 10 km north of Bandung. Lembang Fault is an active fault that has a normal fault type with a movement of 0.3 cm-1.4 cm to the south per year. In research using geophysical methods, the magnetotelluric method is one method that can measure underground resistivity to a depth of hundreds of km. This research was conducted with the aim of studying magnetotelluric method, modeling underground resistivity structure, and interpreting Lembang fault. In magnetotelluric method, four Maxwell equations are used which are derived to obtain impedance, apparent resistivity, phase, and depth of measurement. In data processing, forward modeling and occam inversion are used. For processing 2-dimensional data, the finite difference method is used. In this study, 5 measurement points were taken perpendicular to Lembang fault. Data used has a frequency range from 320Hz to 0.1 Hz. Resistivity The distribution of Lembang fault varies from 1 ohm.m to 330.000 ohm.m. In 1-dimensional inversion there is an increase in resistivity from measurements in the North to the South. In 2-dimensional inversion it can be seen that the high resistivity starting from 25,000 ohm.m appears at around 1000 meters depth. Resistivity distribution map shows an increase in resistivity starting from a depth of 1000 meters from the area around Lembang fault to the southern area of Lembang fault to a depth of 200 meters with highest resistivity in the southern area of 7500 ohm.m. On the surface of Lembang fault suspected an area consist of sedimentary rocks consisting of breccia rocks, lava rocks, and lava rocks. Meanwhile, at a depth of 1000 meters with high resistivity, it is estimated that the basement of Lembang fault has begun to appear.